Graduating from Ethiopia’s Productive Safety Net Programme: What have we learned? - Hirvonen, Kalle; Abate, Gashaw T.; Berhane, Guush; Gilligan, Daniel O.; Hidrobo, Melissa; Hoddinott, John F.; Leight, Jessica; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2025)
Ethiopia’s Productive Safety Net Programme (PSNP) – one of the largest social protection programs in Africa – has improved food security and strengthened recovery from shocks, yet it has achieved limited progress in raising incomes or diversifying livelihoods. In response, policymakers have layered graduation models onto the PSNP to promote sustainable self-reliance. This note synthesizes evaluation evidence from NGO- and government-led initiatives. NGO-led intensive, high-cost models increased assets and incomes in the short to medium term but rarely enabled households to exit the program. NGO-led lighter-touch approaches improved resilience but delivered minimal gains in overall well-being. Government-led efforts have faced persistent delivery challenges, including overstretched systems, weak credit access, and limited market linkages. Broader structural constraints, such as shrinking landholdings, scarce nonfarm opportunities, and recurrent drought and other shocks, further undermine the promise of graduation programming in this context. The review highlights six policy lessons on design, financing, and integration with broader development strategies to shape more effective approaches going forward.